UiTM signs Memorandum of Understanding (MoU) with Dandy Modern Food Sdn. Bhd. / Nor Azlan Othman and Nor Aziyah Bakhari - Othman, Nor Azlan; Bakhari, Nor Aziyah (2021)
A Memorandum of Understanding (MoU) has been signed between Universiti Teknologi MARA (UiTM) and Dandy Modern Food Sdn. Bhd. at the Dandy’s restaurant. The signing of this Memorandum of Understanding will provide further chances for both sides. This relationship is the ideal platform for borderless and global education, as all parties will have the opportunity to produce new knowledge and ideas through a variety of activities and initiatives involving UiTM students and staff and industry partners. In the areas of research development, innovation, curriculum, CSR, human capital, technology, and others, this MoU will serve as a bridge between academicians and industry participants, benefiting staff and students as well as UiTM-Dandy staff.